2011
DOI: 10.19030/cier.v4i11.6486
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study Of Student Attitudes Toward Acceptance Of Online Instruction And Distance Learning

Abstract: This study investigates to what extent student attitudes toward acceptance of online instruction and Distance Learning are affected by determinants such as demographics, learning environment, learning domains, delivery methods, and web-based instructional technology. Logistic Regression and Discriminant Analysis use statistically significant determinants to predict student preference on future online classes. Factor Analysis provides an exploratory model of online learning acceptance having three factors; name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…Until now, many authors have found that students` attitudes may vary in relation to gender, age, nationality, etc. (Beaghan, 2006;Işik et al, 2010;Nguyen and Zhang, 2011;Alam et al, 2012;Fidalgo et al 2020). The findings of this study don`t confirm those conclusions.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Until now, many authors have found that students` attitudes may vary in relation to gender, age, nationality, etc. (Beaghan, 2006;Işik et al, 2010;Nguyen and Zhang, 2011;Alam et al, 2012;Fidalgo et al 2020). The findings of this study don`t confirm those conclusions.…”
Section: Discussioncontrasting
confidence: 65%
“…In addition, the authors emphasized that students found the DL was more effective and comfortable than traditional learning, but at the same time it was boring. Nguyen and Zhang (2011) pointed out that students expressed positive opinions about flexibility, but the most negative attitudes toward the lack of face-to-face communication. In the same study, students ''perceived having heavier workloads' ' (pp.…”
Section: Literature Reviewmentioning
confidence: 99%
“…VLE also contributes to school effectiveness through increasing of the knowledge managements and improvement in skill for knowledge seeking activities. According to Nguyen (2011), the students have to go through VLE based on their own orientation due to unique method of delivery and the class setting [8]. This is due to distance learning via VLE has no face to face communication.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the above-mentioned student characteristics that might affect their choices of course modalities, previous studies have also indicated a potential correlation between students' perceptions of their prior online experience and their choices. (e.g., T. Braun, 2008;Harris & Martin, 2012;Kleisus et al, 1997;Kowalski et al, 2014;Nguyen & Zhang, 2011;Ruffalo, 2016;Thomerson & Smith, 1996;Tseng et al, 2022). Students who have more prior OL experience and felt more satisfied were more likely to choose online courses or courses with online components again (e.g., Artino, 2010;T.…”
Section: The Impact Of Student Characteristics Learning Experiences A...mentioning
confidence: 99%
“…Braun, 2008;K. E. Clayton et al, 2018;Cullum, 2016;Nguyen & Zhang, 2011;Tseng & Walsh, 2016). Given the potential individual and contextual influences on students' choice of learning space reported in the above studies, it is cogent to examine the particular COVID-19 context of this higher education study in Asia.…”
Section: The Impact Of Student Characteristics Learning Experiences A...mentioning
confidence: 99%